Assessment of Dietary Patterns of the Adolescent Pregnant Woman - Haila Malik Sabty, Wisam Mashaan Muttaleb (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Adolescent pregnancy, which is detrimental to the health of mother and child, is a common public health problem worldwide. It is one of the key issues concerning the reproductive health of women not only in developing countries but also in developed countries. There is growing awareness that early childbearing has multiple consequences in terms of maternal health, child health, and the overall well-being of society. Objectives: The study aims to assess the dietary patterns of adolescent pregnant women. Methods: The descriptive study design was conducted on (100) adolescent pregnant women attending the Al-Basrah Maternity and Children Hospital in Al-Basrah Governorate which was selected purposively. The study period was extended from the 1st of February 2022 to the 4th of April 2022. The Questionnaire format developed by the researcher depends on review articles Results: This study showed that (75%) of studied adolescent pregnant women had moderate dietary patterns, (24%) of them had low dietary patterns, and only (1%) of them had high dietary. Conclusions: This study concluded by evaluating all the dietary patterns of pregnant teenage girls that the food patterns were somewhat acceptable to pregnant teenage girls.